Limb length restoring through novel limb salvage procedure via ipsilateral fibular strut autograft: A case report - Emily B. Stefanski, DPM; Douglas J. Glod, DPM; Lee M. Tiberi, DPM; Alexander A. Trottier, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases)
Limb salvage procedures can be complicated by large segmental defects. Aggressive tibio-talar debridement or possible talectomy, hardware removal, and revisional surgery often leave a large void. An ideal graft that is mechanically strong, readily available, disease free, capable of maintaining length, and possesses all three biologic properties (osteoinductive, osteoconductive and osteogenic) is difficult to find. 3D printed implants and allografts, such as femoral head, are viable options but may present with pitfalls such as increased cost and risk of nonunion. This case report outlines a novel limb salvage surgical technique for tibiocalcaneal arthrodesis with an ipsilateral fibular strut autograft. The harvested fibula is divided into struts, which are then assembled into a circular configuration and used to fill a large defect. This technique offers an accessible and affordable solution of providing both substantial bone graft to assist in tibiocalcaneal arthrodesis, while also maintaining length.